Millennial Vs Gen Z: Tax Knowledge, Tax Education, and Tax Compliance - Hidayati, Berlina; Utami, Indah Setia (CV ODIS, 2024)
This research aims to compare how Millennials and Gen Z view tax knowledge, tax education, and tax compliance so educators can develop more effective tax education programs. This research uses a quantitative study by using 804 students of the Taxation Department at Universitas Terbuka as respondents and uses comparative analysis. This finding shows that social media behavior, speed in obtaining information, and demands for solving problems creatively and innovatively, can be important factors that influence these significant differences. This fact confirms that skills in utilizing information and communication technology to understand and solve problems will encourage them to get information in tax knowledge, tax education, and tax compliance, even though this is greatly influenced by each individual's self-regulated learning.